An Elitist Local Search Based Multi-objective Algorithm for Power Distribution System Reconfiguration - Leon Ibarra, Marco Antonio; Guardado, Jose Leonardo; Rivas-Davalos, Francisco; Torres Jimenez, Jacinto; Naredo, Jose Luis (Electric power components and systems, 2016)
This article proposes a new evolutionary algorithm for power distribution system reconfiguration considering a multi-objective optimization approach. The proposed algorithm is based on the use of local searches distributed strategically along the Pareto front. The combination of local searches with elitism improves the convergence speed, diversity, and quality of the solutions found. The performance of the algorithm was successfully tested on several distribution systems, and the results show an improvement over those provided by other techniques. The objective functions to optimize are typical of distribution systems: power losses, voltage deviation, system average interruption frequency index, system average interruption duration index, energy not supplied, and customer average interruption duration index.